Ceramic Ethnoarchaeometry in Western Sardinia: Production of Cooking Ware at Pabillonis. (25th April 2014) - Cau Ontiveros, M. Á.; Montana, G.; Tsantini, E.; Randazzo, L.
<x xml:space="preserve">Abstract</x> Ceramic ethnoarchaeology has been used to explore fully the chaîne opératoire and to understand all of the stages and factors involved in pottery production, such as raw material selection or paste recipes used by the potters. This work presents the results of the application of compositional analysis undertaken in the village of Pabillonis (western Sardinia, Italy), the main cooking ware production centre of the island. Pottery and local clays have been characterized using a combination of analytical techniques. By integrating the ethnographic information and the archaeometric approach, it was possible to reconstruct the operational sequence, exploring the relationship between the processing of raw materials and the functionality of the final products, and the intra‐production compositional variability.